Implementation of Evidence-Based Medicine: Evaluation of the Promoting Action on Clinical Effectiveness Programme - Dopson, S; Locock, L; Chambers, D; Gabbay, J (2001)
Objectives: To evaluate the Promoting Action on Clinical Effectiveness (PACE) programme, which sought to implement clinically effective practice in 16 local sites. Methods: 182 semi-structured interviews, usually by telephone, with project team members, clinicians, and senior managers and representatives from the Department of Health and the King's Fund. Results: The most influential factors were strong evidence, supportive opinion leaders and integration within a committed organization; without these factors, projects had little chance of success. Other factors (context analysis, professional involvement and good project management) emerged as important, supporting processes; their presence might be an additional help, but on their own they would not be enough to initiate change. A serious problem with any of them could have a strong adverse impact. Conclusions: Although there is no simple formula for the factors that ensure successful implementation of research-based improvements to clinical practice, certain principles do seem to help. Time and resource need to be devoted to a period of local negotiation and adaptation of good research evidence based on a careful understanding of the local context, in which opinion leader influence is an important component of a well managed and preferably well integrated process of change.